EFFECTIVENESS OF THE FLASHED LEARNING MODEL IN PRIMARY SCHOOL STUDENTS - Sukma, Megan; Subandi, Oman Unju; Rihatno, Taufik (Gladi : Jurnal Ilmu Keolahragaan, 2024)
The aim of this research is to test the effectiveness of the throwing learning model for students at SDN Bintara Jaya IV. The method used in this research is a pre-experimental method with one sample group, namely the experimental group who received throwing lessons. The research design is in the form of a one group pretest-posttest design. The instrument used in this research uses a throwing motion assessment instrument. The research results showed that the average gain score for the experimental group was 0.864 (86%) and the control group was 0.330 (33%) . Based on this information, it can be said that the throwing learning model can improve throwing learning outcomes.